Kreativitas Guru PAI dalam Menggunakan Metode Pembelajaran untuk Menciptakan Pembelajaran Efektif di SDN 13 Lubuk Alung - Khairani, Annisa; Rahman, Rini (Asian Journal of Islamic Studies and Da'wah, 2023)
Burnout in learning is an unpleasant emotional condition that arises when individuals engage in monotonous activities. Islamic Religious Education (PAI) subjects are often considered less engaging, causing students to become bored and disinterested. Therefore, it is crucial for PAI teachers to employ creative teaching methods to establish effective learning environments. The method utilized in this study is qualitative with a descriptive approach. Data sources were gathered from PAI teachers, fourth-grade homeroom teachers, and fourth-grade students through observations, interviews, and documentation. Data analysis techniques involved reduction, presentation, and conclusion/verification processes. Further data validation was carried out by expanding observations and using triangulation. The primary objective of this research is to illustrate the creativity of PAI teachers in employing methods that foster effective teaching and learning environments. The results of this research demonstrate PAI teachers' creativity in using methods, which includes the integration of multiple suitable methods to create effective teaching and learning environments at SD N 13 Lubuk Alung.